(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
‘Opinion leaders’ and ‘personal influence’ seems to be the main concepts associated with Paul Lazarsfeld in media research, as the main ingredients of the ‘two-step flow’ model of communication, developed in milestone books The People’s Choice (1948), Voting (1954) and Personal Influence (1955). Although familiar in Communication Theory, these notions are not always presented in a greater length. This paper, grounded on a reading of the books, highlights other aspects of Lazarsfeld’s model that seems to have been less discussed in the area’s literature: (1) the importance of small groups in communication; (2) how opinion leaders emerge from trust relations inside groups and (3) the risks of opinion homogenization and political polarization related to the leaders influence inside groups. These elements are discussed against the background of communication epistemology studies.